Factors contributing to students' satisfaction in blended learning / Nurul Nadiah Ibrahim ... [et al.] - Ibrahim, Nurul Nadiah; Ahmad, Emmarelda Maswesi; Abdul Aziz, Rozainun; Kamaluddin, Amrizah (2018)
The emergence of Information Technology (IT) has brought the education system into a world of new dimension and the emphasis is now on educating the Millennials and Generation Z. This unique generation demands for a more fun and digitalised approach when it comes to learning (Kotz, 2016). This study examines students' factors of satisfaction in blended learning courses. Students' factors of satisfaction were assessed in four areas that were deemed important to the university: technology, interaction, content and motivation. The overall satisfaction with blended learning were the dependent variable. This study used primary resources where questionnaires were distributed to final semester students in Universiti Teknologi MARA (UiTM) as they have a vast experience in using a blended learning tool called 'i-Learn'. The findings showed that there is a strong relationship between the factor of technology, interaction, content and motivation on the students' satisfaction in blended learning. This shows that students were overall satisfied with the current blended learning that is being implemented in UiTM. Therefore, when scaling up blended learning, institutions may want to consider offering students a choice of whether to enroll in blended or fully face-to-face course sections where feasible, especially in subject areas that students find to be difficult.